Transitivity Analysis of University News Texts during the Coronavirus Pandemic: Transitivity Analysis of University News Texts - Alhumsi, Mohammad Husam; Suliman, Elbadri A.; Sendi, Kholod K.; Alshaye, Rasha A. (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
Halliday’s theory of transitivity can describe the specific linguistic characteristics through which the text can be fully comprehended by readers in a manner that reveals the writer’s intention. This study concentrates on the analysis of various process types. It investigates the effectiveness of transitivity theory in the analysis of transitivity processes by comparing two news texts published in the Saudi Electronic University (SEU) website before and during the pandemic. To raise critical awareness of the characteristics of news discourse, this paper employs critical discourse analysis tools. To explore the processes of transitivity, quantitative and qualitative approaches were adopted. The findings revealed that material processes are the most frequent processes in the two news articles produced. The study provides recommendations for further studies.